2003
DOI: 10.1080/03610730303716
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Fear of Crime: An Experimental Approach to an Apparent Paradox

Abstract: Many fear of crime studies have revealed an interesting paradox: Although older adults are less likely to be victims, they report a higher fear of crime than younger adults. In this study, we experimentally manipulated vicarious exposure to crime. Younger (ages 18-29) and older adults (ages 61-78) were randomly assigned to view either a vivid video reenactment of a violent crime or a crime report newscast. Subjects in the violent video condition demonstrated significantly higher fear than did control group par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…Females felt less in control than males and judged the consequences to be higher; they judged likelihood to be higher and felt that their own social group was more likely to fall victim than other social groups. This study also found that younger people worried more frequently than older people about personal crime (but not about property crime) -a finding consistent with the studies of Akers, La Greca, Sellers, and Cochran (1987), Chadee and Ditton (2003), Ferraro and LaGrange (1992), LaGrange and Ferraro (1989) and Ziegler and Mitchell (2003) -but contrary to gender, these differences could not be explained by differential vulnerability or likelihoodperception. And further investigation -which differentiated between personal and property crime -showed that females worried more frequently than males about personal crime, but that there was no gender difference in worry about property crime.…”
Section: Discussionsupporting
confidence: 88%
“…Females felt less in control than males and judged the consequences to be higher; they judged likelihood to be higher and felt that their own social group was more likely to fall victim than other social groups. This study also found that younger people worried more frequently than older people about personal crime (but not about property crime) -a finding consistent with the studies of Akers, La Greca, Sellers, and Cochran (1987), Chadee and Ditton (2003), Ferraro and LaGrange (1992), LaGrange and Ferraro (1989) and Ziegler and Mitchell (2003) -but contrary to gender, these differences could not be explained by differential vulnerability or likelihoodperception. And further investigation -which differentiated between personal and property crime -showed that females worried more frequently than males about personal crime, but that there was no gender difference in worry about property crime.…”
Section: Discussionsupporting
confidence: 88%
“…However, certain facets of age might be particularly relevant to fear of crime, including history of personal victimization (Acierno et al 2003;McCoy et al 1996;Mesch 2000) and vicarious victimization. Indeed, compared to younger adults, older adults are more likely to have been victims (Greve 1998) and to have known a victim (Ziegler and Mitchell 2003).…”
Section: Aging and Fear Of Crimementioning
confidence: 99%
“…If an older person feels out of synchrony with the environment, fear of crime can increase (McCoy et al 1996). Compared to younger adults, older adults were less afraid of crime in the home and more afraid of neighborhood crime (Ziegler and Mitchell 2003).…”
Section: Environment and Fear Of Crimementioning
confidence: 99%
“…Thus public perception of numerous `Extra-familial' assailants is far from the actual reality, as is the case with other high profile deaths, as fear and perception of violence is so often disproportionately higher than the reality (Pritchard & Evans, 2001;Zieglere & Mitchell, 2003;Pritchard & Wallace, 2006). Conversely, contrasted against UK child cancer and accidents, the VMCCSA men are especially dangerous and perhaps pose an unacceptable level of physical risk to children?…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Public perception of the risk of violence against children, influenced by media stereotyping, is very much at odds with statistical reality (Zieglere & Mitchell, 2003), exemplified by public attitudes to mental disorder following the Hungerford killings (Appleby & Wessley, 1998). Indeed, other instances of just how far public misperception of violent death is at odds with reality, is found in the fact that there were more homicides in the USA during the Viet-Nam war than the numbers of American casualties in that war (Fast & Page 1997;Pritchard & Evans, 2001) and, compared to the September 11 th 2001 tragic toll of 3,074 people, more people die annually from suicide in Britain (Pritchard & Wallace, 2006), whilst every two-weeks more people die in the USA from homicide, suicide and road deaths than died on 9/11.…”
Section: Introductionmentioning
confidence: 99%